Heart and kidney crosstalk: risk factors, clinical features, and short-term outcomes associated with acute kidney injury in patients suffering acute non-ST elevation myocardial infarction - Minela Becirovic; Emir Bećirović; Semir Hadžić; Lejla Rakovac Tupković; Amir Bećirović; Nadina Avdić Jahić; Aida Ribić; Lamija Ferhatbegović; Amira Jagodić Ejubović; Emir Begagić; Daniela Lončar; Kenana Ljuca (Medicinski glasnik, 2025)
Aim: Acute kidney injury (AKI) presents a high mortality complication in patients with acute myocardial infarction (AMI). Yet, its correlation with non-ST elevation myocardial infarction (NSTEMI) remains neglected in the literature. This study aims to investigate the prevalence, risk factors, clinical features, and short-term outcomes associated with AKI development in patients with acute NSTEMI. Methods: A one-year prospective observational cohort study involved 170 consecutive patients hospitalized in the Intensive Care Department of the Internal Medicine Clinic at the University Clinical Centre Tuzla diagnosed with acute NSTEMI. Patients were subsequently categorized into AKI and non-AKI groups based on AKI development within 48 hours. Demographic characteristics, laboratory findings, and short-term clinical outcomes were compared between the groups. Results: Of 170 patients, 31 (18.2%) developed AKI within 48 hours of acute NSTEMI. Significant age differences, blood urea nitrogen (BUN), creatinine, estimated glomerular filtration rate (eGFR), blood glucose level (BGL), C-reactive protein (CRP), and high sensitivity (hs) troponin were observed, making patients with lower baseline kidney function, more extensive myocardial infarction, and a heavier systemic inflammatory response following acute NSTEMI more susceptible to AKI development. In the follow-up period, mortality rates were significantly higher in the AKI group, amounting to 35.5% compared to 10.1% in the non-AKI group. Additionally, mortality increased with the severity of AKI, reaching 100% in AKI stage 2. Conclusion: This study highlights demographic, clinical and laboratory findings in patients with acute NSTEMI, which contribute to AKI development. Early detection and tailored interventions are crucial in mitigating AKI-associated morbidity and mortality.
Keywords: cardiac biomarkers; intensive care unit; kidney failure; myocardial ischemia